From Text to Relics: The Emergence of the Scribe-Martyr in Late Antique Christianity (Fourth Century–Seventh Century) - Inowlocki, Sabrina (Journal of early Christian studies, 2024)
This paper delves into the conflation of two prominent figures of authority in the early Christian world: the scribe-scholar and the martyr. While previous scholarship has largely examined these figures separately, this study focuses on their association and argues that they were meaningfully combined to establish a new form of textual authority. The motif of the scribe-martyr is explored in a series of Christian texts, from Pseudo-Pionius to John Moschus and late ancient hagiographic texts, tracing its origins to the fourth century. This development emerged from the growing association between the authority of written texts as physical objects and the rise of the cult of saints and their relics. In parallel with Foucault’s concept of the author-function, a distinct Christian “scribe-function” emerged within this context, i.e., discourses of authority, fictitious or historical, involving the individuals who reproduced or corrected texts. The paper posits that the motif of the scribe-martyr was then strategically employed in legal, scholarly, and institutional contexts to express faithfulness, resistance, authorization, and legitimation. As a result, this conflation contributed significantly to the attribution of holiness and authority to texts, sacred places, and religious institutions. Thus, the scribe-martyr, connected to the revered relic-texts, assumed a particularly potent role as a figure of theological authority within late ancient Christianity.